2018
DOI: 10.1002/aocs.12130
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Points Related to the Lag Phase of Fungal Growth in a Stored Rapeseed Ecosystem

Abstract: The quality of rapeseed oil largely depends on the quality of postharvest preservation of raw seeds. Fungal infestation at early stages of the storage of rapeseeds is a major cause of their spoilage. The knowledge of relations between the storage conditions, fungal contamination, and technological quality of rapeseeds is essential to specify key control points that can be used to improve postharvest management systems and maintain rapeseed quality. The aim of this study was to define decisive control points on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…the lag phase, exponential growth and the stationary phase. A similar pattern of mould development was observed in barley grain and rapeseed ecosystems by Wawrzyniak et al (2013;2018a;2018b). The decrease in CFU of moulds in the initial period of seed storage (in the lag phase of mould growth) was associated with the fungi's adaptation to environmental conditions.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…the lag phase, exponential growth and the stationary phase. A similar pattern of mould development was observed in barley grain and rapeseed ecosystems by Wawrzyniak et al (2013;2018a;2018b). The decrease in CFU of moulds in the initial period of seed storage (in the lag phase of mould growth) was associated with the fungi's adaptation to environmental conditions.…”
Section: Resultssupporting
confidence: 68%
“…While investigating the rapeseed ecosystem with a moisture content of 13.1% w.b. stored at 24°C, Wawrzyniak et al (2018a) also observed the beginning of fungal activity after 6 days of storage, whilst the stationary phase of the mould development began after 18 days.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…It may be utilized for consumption, in the food industry or for non-food purposes. The production of rapeseed in the European Union has exceeded 20 million tons/year and accounts for about 30% of global oilseed production (Wawrzyniak et al, 2018). Rapeseed oil, due to its fatty acid composition, is considered to be one of the healthiest vegetable oils.…”
Section: Introductionmentioning
confidence: 99%